Practical Recommendation of the Scientific Сommunity for Human Microbiome Research (CHMR) and the Russian Gastroenterological Association (RGA) on Small Intestinal Bacterial Overgrowth in Adults - V. T. Ivashkin; I. V. Maev; D. I. Abdulganieva; O. P. Alekseeva; S. A. Alekseenko; O. Yu. Zolnikova; N. V. Korochanskaya; O. S. Medvedev; E. A. Poluektova; V. I. Simanenkov; A. S. Trukhmanov; I. B. Khlynov; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. To optimize the choice of treatment strategies by physicians and gastroenterologists to improve treatment and prevention of small intestinal bacterial overgrowth (SIBO) in adults.Key points. SIBO is a condition characterized by an increased amount and/or abnormal composition of the microbiota in the small intestine. Clinically, the syndrome is manifested by nonspecific gastroenterological complaints and the development of malabsorption syndrome. Most often, SIBO is associated with various chronic non- infectious diseases (both diseases of the gastrointestinal tract, and the cardiovascular system and the neuromuscular apparatus) and can affect the severity of their symptoms. Specific methods for diagnosing SIBO are the culture method and breath tests. The main approaches to the treatment of SIBO include the elimination of the underlying cause of its occurrence, the use of antibacterial drugs and adherence to dietary recommendations (elemental diet).Conclusion. Small intestinal bacterial overgrowth is common in patients with various diseases, but has non-specific manifestations, so proper diagnosis of this condition is required. SIBO therapy involves prescription of antibacterial agents, the most studied of which is the non-absorbable antibiotic rifaximin-α.